2003
DOI: 10.1063/1.1540633
|View full text |Cite
|
Sign up to set email alerts
|

Wall-pressure-array measurements beneath a separating/reattaching flow region

Abstract: A database of wall-pressure-array measurements was compiled for studying the space–time character of the surface-pressure field within a separating/reattaching flow region. The experimental setup consisted of a long splitter plate located within the wake of a fence and instrumented with an array of flush-mounted microphones. Data were acquired for a Reynolds number of 7900, based on the fence height above the splitter plate. Two distinctive regions, defined based on their location relative to the position of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 20 publications
7
57
1
Order By: Relevance
“…In this case, it is interesting to note that the −1 and the − 7 3 scalings coexist. Results obtained at different positions upstream ͑not shown here͒ confirm that the − 7 3 decay law becomes predominant as the distance to the step decreases. It is also observed that such a behavior is independent of Re h since the two scalings are equally present for the whole set of velocities.…”
Section: B Wall Pressure Statisticssupporting
confidence: 84%
See 2 more Smart Citations
“…In this case, it is interesting to note that the −1 and the − 7 3 scalings coexist. Results obtained at different positions upstream ͑not shown here͒ confirm that the − 7 3 decay law becomes predominant as the distance to the step decreases. It is also observed that such a behavior is independent of Re h since the two scalings are equally present for the whole set of velocities.…”
Section: B Wall Pressure Statisticssupporting
confidence: 84%
“…Downstream of the step up to about x / h = 3.5, we observe a larger dispersion that is associated with the varying dimensions of the recirculation region, which are affected by Re h . A similar result was obtained, for instance, by Hudy et al 7 and Cherry et al 24 The analysis of the instantaneous velocity fields provided by the time-resolved PIV measurements confirms that the position of the flow reattachment is strongly time dependent. The maximum amplitude of the Cp rms coefficient is found to correspond approximately to the location of the mean reattachment point of the recirculation bubble.…”
Section: B Wall Pressure Statisticssupporting
confidence: 72%
See 1 more Smart Citation
“…In the shear layer near the leading edge (P01), we observed a peak at lower frequency f 1 = 0.25U ∞ /c, corresponding to approximately half the shedding frequency and related to a low frequency flapping motion of the shear layer. 35,[38][39][40][41] In the same spectrum, a third peak is present at f 4 = 9.75U ∞ /c corresponding to the vortex generation due to the leading edge Kelvin-Helmholtz (KH) shear layer instability. Another smooth peak at frequency f 3 = 2.52U ∞ /c is present in the spectrum corresponding to the midchord location (P02).…”
Section: A High Angle Of Attackmentioning
confidence: 92%
“…Bitter et al 11 performed measurements at Mach = 0.7 and presented also a value of 3.7 for this quantity. Low speed experiments also showed a decreased length of the reattachment location 12,13 indicating that the round shape of the model reduces this quantity significantly. The flow over a cylindrical forebody elongated by a second cylinder of smaller diameter and finite length was in the focus of several numerical investigations [14][15][16][17] and of experiments presented in Depres, Reijasse, and Dussauge 18 .…”
Section: Review Of Previous Experimentsmentioning
confidence: 94%